O papel do setor florestal para a conservação da vegetação nativa no entorno de áreas protegidas - Queiroz, Daniela Aparecida Rosa de (2022)
Protected areas are essential for the conservation of biodiversity and ecosystem services. However, the conservation of these areas also depends on the management of their surroundings, enabling the connectivity of the landscape with native species. In agricultural landscapes, the preservation of native vegetation on rural properties is one of the indispensable means for the connectivity of the protected area. Certifications in the forestry sector that require compliance with environmental laws can work as an important instrument to maintain or improve the conservation of protected areas in the agricultural landscape. Thus, the objective of this study was to assess changes in land use/cover and landscape connectivity around the Capão Bonito National Forest (FNCB) in southeastern Brazil between 1986 and 2019 and to understand whether the forest sector has contributed to maintaining vegetation. native to private lands. For this, we evaluated land use and land cover in 1986, 2008 and 2019, focusing on the application of the so-called New Forest Law (NLF). We obtained land use and land cover maps from Mapbiomas and verified land use change using the Arcgis 10.5 raster calculator tool. The connectivity of the landscape and the importance of the surrounding native vegetation fragments was verified based on the Graph Theory. Property boundaries were extracted from a land tenure model for the State of São Paulo. To verify the perception of landowners and forestry companies, we sent a questionnaire with open and closed questions. Our results showed that pasture and native vegetation were the main land use/cover in the area. Forest plantation occupied a significant area around and within the protected area. In terms of property numbers, forestry plantations had the largest area of properties in 2019, and the largest native vegetation cover over the years in relation to other agricultural sectors. Forest fragmentation has increased over the years, even with the increase in native vegetation in 2019 compared to 2008. Regarding intent and compliance with the NLF, owners and companies have demonstrated knowledge and intent to comply with the law. Regarding the knowledge of the FNCB, most respondents said they did not know about the existence of this conservation unit. Among the companies in the forestry sector, they reported having actions involving the FNCB, and there are other actions under study; most respondents are Forest Stewardship Council (FSC) certified. The results obtained provide an important subsidy for the management of the conservation unit, with diagnosis for knowledge and possible improvement in the awareness and interaction of rural owners and forestry companies with the conservation unit.